LV and MV polymeric insulated cables for use by distribution and generation utilities. Specification for distribution cables with extruded insulation for rated voltages of 11 kV and 33 kV. Three-core 11 kV cables Part 4.20, (15th August 1999) - British Standards Institution,
No abstract available